Factors Affecting Shopee Sellers Competitive Advantage And Company Performance - Lalu Supardin; Rinaldi, Rinaldi; Sri Rejeki Ekasasi (Sean Institute, 2024)
The purpose of this study is to determine the impact of gamification on the competitive advantage and commercial performance of Shopee vendors. This study utilized a quantitative approach. One hundred Shopee vendors who use gamification techniques to improve their overall business performance and competitive advantage are the research sample. The sampling procedure used a non-probability sampling approach combined with purposive sampling techniques. In this study, the data collected through the distribution of Google Form questionnaires were processed and assessed using the PLS-SEM tool. The first finding, from this study, shows that gamification increases competitive advantage in the Shopee app. The second finding, from this study shows that gamification improves company performance in the Shopee app. The last finding, from this study shows that that gamification increases competitive advantage through company performance in the Shopee app.